Customized Education Artificial Intelligence's Role In Tailored E-Learning. - Kanbur, Gaurang; Meenakshi Thalor (MultiTech Publisher, 2023)
This research is driven by the immense potential of personalized e-learning systems to address the challenges of effective online education delivery. It focuses on proposing an efficient architectural framework for personalized e-learning systems, exploring various techniques and challenges and offering innovative solutions. The paper conducts a thorough review of current state-of-the-art methodologies in implementing personalized e-learning systems, along with discussions on the crucial requirements and challenges for successful deployment. Furthermore, it presents an efficient framework for building effective e-learning systems, while also discussing mechanisms, challenges and future research directions that the research community can consider. The subsequent sections of this paper provide a detailed exploration of the research, followed by a proposal for a personalized learning system, and insights into important issues for the community to address. The paper concludes by summarizing its findings and contributions.